Gender and medication use in Turkey: Evidence from a general population survey - Tekin Kose (PLoS ONE, 2025)
Gender differences in health behaviors and outcomes were commonly documented by researchers. The focus of this study was the analysis of gender differences in medication use for a general population in Turkey. It also explored a range of factors associated with medication use at the individual level. A nationally representative cross-sectional data set was obtained from the 2019 wave of the Turkish Health Survey. The sample of this study included 17,083 adults residing in different regions of Turkey. Conditional mixed-process regression models were estimated for the whole sample and subsamples by gender. The rates of prescribed and non-prescribed medication use were 40.7% and 30.2%, respectively, in the adult population of Turkey. There were significant gender differences in medication use in the Turkish case. Females were 19.4% more likely to use prescribed medication, and they were 30.8% more likely to use non-prescribed medication compared to males in Turkey. There were negative associations between prescribed and non-prescribed medication use. On average, females were 9.2% less likely to report higher levels of health status, and they were 18.4% more likely to use healthcare services. Individuals with higher levels of self-rated health status were less likely to use prescribed medication. Both prescribed and non-prescribed medication use were positively related to healthcare service use. Complementing the earlier literature, the results of the present study demonstrated that gender-specific designs should be considered by health policies on the use of medications.